Approaches to Topical Issues in Music and Aesthetic Education of Students - Smirnov, Alexander V.; Grigorieva, Elena I.; Illarionova, Nadezhda N.; Shcherbinina, Valentina M.; Yushchenko, Natalia S. (International Review of Management and Marketing, 2016)
The paper presents different educational systems to work out effective approaches to solving the problems in music and aesthetic education of students. Thus, one of the main tasks in the professional activity of a music educator is to master unique methods of optimizing the education process that will make it possible to educate a brilliant musician from a music gifted student within the shortest period. Modern person-oriented approach to education provides for the creation of a favorable art environment for music and aesthetic and personal development of each student and taking him as a creative personality. A training and creative team on the basis of a music performing class provides for a flexible dynamic content of education with regard to its updating due to call of the times, and aims at solving vital tasks – comprehensive education of a free personality with independent humanistic worldview, early personal identity and professional orientation of students, split-level education developing personality, full pre-professional education. The goal of a training and creative team is to update the pedagogical process conceptually and practically with regard to its focus on a student's personality and at the same time on a teacher, development of his professional activity and music education in whole. Optimal psychological and pedagogical conditions are created in a music performing class to develop students' intellectual, moral, social and personal qualities. Special co-creative spirit generated in such team is able to establish a favorable situation to solve topical issues in music and aesthetic education of students, the best of which will become worthy representatives of the cultural social elite. Keywords: Training and creative team; music performing class; music educator; accelerated training JEL Classifications: Z11, Z00, Z10